(untitled) (Tempo e Argumento, 2012)
This paper runs upon the analyses of the research entitled “The school and the youth in the contemporary world: processes of Latin American historic formation” developed in two schools in the city of Florianópolis from 2009 to 2011. These public schools are the training field of initial formation of History teachers in the Federal University of Santa Catarina. The empiric research was developed with the youngsters of the seventh grade of Elementary School and investigated the building of the Latin American historic consciousness. This article focuses on the relation between the curricular choices for the History Teaching of both schools, and the inference in the students’ narratives about the Latin American History. A conceptual reading of the curriculum is tempted, through the Cultural Studies that allows the perception of political tensions in the construction of a belonging feeling and the youth identities that were presented in their narratives about the Latin America. The analyses presented bring the fights for the memories and identities to surface, inside the curriculum, which guide the youngsters’ life and their future perspective building. In this movement, choices that are made determine the knowledge according to the subjects and identities that are wished to be built.